The Implementation of the Problem-Based Learning Model to Improve Students' Learning Interest in Pancasila Education Among Fourth-Grade Students at SDN 3 Lambara - Salsa Bila; Arif Firmansyah; Muchdar Muchdar; Herlina Herlina; Muslim Muslim (FKIP - Universitas Riau, 2026)
This study was motivated by the low learning interest of fourth-grade students in Pancasila Education at SDN 3 Lambara, as reflected in their limited participation, attention, and engagement during classroom learning. The study aimed to improve students' learning interest through the implementation of the Problem-Based Learning (PBL) model. This study employed Classroom Action Research conducted in two cycles, each consisting of planning, action, observation, and reflection. The participants were 28 fourth-grade students. Data were collected through observations of teacher and student activities and a learning interest questionnaire, then analyzed using descriptive qualitative and quantitative techniques. The findings demonstrated that the implementation of the PBL model effectively improved students' learning interest. Classical learning mastery increased from 33.33% in the preliminary stage to 66.66% in Cycle I and 91.66% in Cycle II. Furthermore, teacher and student learning activities improved from the good to the very good category across the research cycles. These findings indicate that the Problem-Based Learning model creates a more active, collaborative, and meaningful learning environment, thereby effectively enhancing students' learning interest in Pancasila Education among fourth-grade elementary school students.